Validated RP-HPLC Method for the Determination of Mycophenolate Mofetil in Tablet Dosage Forms - Vijaya Bhaskara Reddy, T.; Ramu, G.; Sravan Kumar, M.; Rambabu, C. (Asian Journal of Chemistry, 2013)
A precise, accurate and more sensitive RP-HPLC method is developed to estimate the amount of mycophenolate mofetil in pure and tablets using Waters-Alliance HPLC system equipped with auto sampler and ultra-violet detector. The method is carried out on a Symmetry C18 (4.6 mm ID × 150 mm, 5 μm, Make: XTerra) with a mobile phase consisting of acetonitrile and potassium dihydrogen phosphate buffer of pH = 4.0 in the ratio 65:35 volume/volume at a flow rate of 0.7 mL/min. The detection of eluted components is carried out at a wavelength of 216 nm. The retention time of mycophenolate mofetil is found to be 2.647 min. The developed method is validated in terms of accuracy, precision, linearity, limit of detection, limit of quantization. The linearity limits, LOD and LOQ of the developed method are found to be 10-50, 0.052 and 0.171 μg mL-1, respectively. The developed method is found to be simple, fast and economic and hence it can be used as an alternative method in quality control.